The Blurry Portrait of Drug Abuse and Illicit Drug Trafficking in Indonesian Prisons - Christiana, Christiana; Runturambi , Arthur Josias Simon (Technium Social Sciences Journal, 2023)
The problem of drug abuse and trafficking in prisons is a phenomenon that often occurs in prisons. Indonesia is one of the countries experiencing prison overcrowding with most of the prison population being drug abuse cases. This research uses the literature study method by tracing journals, mass media coverage and other related literature. The results of the search stated that the phenomenon of drug abuse and trafficking in prisons is often reported. The existing news is an iceberg phenomenon. Therefore, the imprisonment policy for drug cases, especially drug abusers, needs to be considered because it does not have a deterrent effect. On the contrary, they can develop from abusers to dealers. A health approach for drug abusers should be considered.